A review of species of the genus Apalochrus Erichson (Coleoptera, Malachiidae) - Tshernyshev, Sergei E. (Zootaxa, 2015)
The genus Apalochrus Erichson, 1840 (Coleoptera, Cleroidea, Malachiidae) is revised. All seven species and subspecies of the genus have been discussed and described, all materials studied have been listed and the known distributions reported. Figures of male habiti, genitalia, and distribution map are supplied; a determination key is also provided. One new status and two new synonymies are proposed: A. femoralis pallipes Motschulsky, 1860 stat. n.; A. flavicornis Abeille de Perrin, 1890 = A. femoralis pallipes Motschulsky, 1860 syn. n. and A. notatus mongolicus Evers, 1968 = A. notatus (Zoubkoff, 1833) syn. n.